Ätiologie des Zervixkarzinoms und dessen Vorstufen - Reuschenbach, Miriam; Vinokurova, Svetlana; Knebel Doeberitz, Magnus von (Der Onkologe, 2012)
Infections with human papillomavirus (HPV) are a very common occurrence in both women and men. The HPV-associated cancer precursors or even invasive carcinomas occur only rarely in comparison to the number of infectious events. Under this aspect it is particularly conspicuous that although men and women go through comparably common rates of genital HPV infections, tumors developing from this occur in the vast majority of cases in the transformation zone of the cervix uteri. The pathogenic activity of HPV therefore seems to be greatly dependent on the special characteristics of infected host cells. Epigenetic mechanisms play a substantial role in the control of viral gene expression. In particular the transition from the permissive, virus-producing infectious stage to the transforming stage, in which neoplastic alterations can arise due to expression of the viral oncogenes, seems to be associated with certain methylation patterns of the viral genome which promote expression of the E6 and E7 oncogenes. The transforming stage is seen as the actual carcinogenic event and can be detected immunohistochemically by the biomarker p16INK4a in all affected cells.